Integrative transcriptomic, proteomic, biochemical and neutralization studies on the venom of Micrurus ephippifer - Zarzosa, Vanessa (2025)
Species of the genus Micrurus belong to the family Elapidae and possess venoms of significant clinical importance.This study presents an analysis of the venom composition of Micrurus ephippifer, employing transcriptomicand proteomic methodologies. A total of 2885 venom gland transcripts were assembled, of which 42 wereidentified as toxins. Transcripts for three-finger toxins (3FTx) were the most abundant (80.7 %), followed byPLA2 transcripts (16.3 %). Tryptic peptide sequences obtained through bottom-up shotgun MS/MS venomanalysis were assigned to 46 distinct proteins in the SwissProt/UniProt database, of which 23 belong to the 3FTxfamily. Peptide spectral matching against the venom gland transcriptome database identified 24 proteins, 12 ofwhich correspond to 3FTx, and three belong to PLA2. Venom decomplexation by RP-HPLC followed by N-terminalamino acid sequencing of fractions allowed an estimation of the relative abundance of protein families,indicating that 3FTx comprise over 50 % of the venom. The identified toxic fractions displayed distinct lethalityprofiles in mice, with certain combinations exhibiting enhanced toxicity, very similar to what has been reportedwith Brownitoxin-I, with only the PLA2 sequence showing similarity. Our results emphasize the importance ofintegrating transcriptomic and proteomic approaches to understand venom diversity and its implications forantivenom development.Significance: Mexico ranks first in the Americas in snake venom diversity. Paradoxically, very little is knownabout the composition of coral snake venoms, and Micrurus ephippifer is a clear example of this gap, as nothingwas known about its venom composition. This type of study provides valuable information that helps fill theseknowledge gaps. This study presents the second report of coral snake venoms containing a complex of phospholipaseA2 and a three-finger toxin, offering important data that, with further research, will contribute tounderstanding venom evolution and evaluating the efficacy of antivenoms.